2020
DOI: 10.1055/s-0040-1713690
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in Electrolyte Measurements by Direct and Indirect Ion Selective Electrodes due to Interferences by Proteins and Lipids

Abstract: Objectives We aim to report the simultaneous effect of different protein and lipid concentrations on sodium (Na+) and potassium (K+) measurement by direct and indirect ion selective electrodes (dISE and iISE) in patient samples. Materials and Methods Na+ and K+ were measured in 195 serum samples received in the laboratory using iISE by Roche Modular P800 autoanalyzer and using dISE by XI-921 ver. 6.0 Caretium electrolyte analyzer. Serum total protein (TP), cholesterol (Chol), and triglycerides (TG) were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The Prime Plus VET analyzer met all manufacturer quality control targets during the study, indicating that the increased variability was most likely the result of matrix effects. Interestingly, we could identify only two studies that compared measurements of serum or plasma electrolytes using direct and indirect ISE methods, and both studies reported a similar degree of variability in measuring Na concentration 15,16 to that observed in our study, suggesting the presence of a matrix effect. The increased variability in our study was not due to abnormal total protein concentrations, but because linear regression did not identify a significant relationship between the difference in serum Cl, K, and Na concentrations measured by the Prime Plus VET and Beckman chemistry analyzers and serum total protein concentration.…”
Section: Discussionsupporting
confidence: 68%
“…The Prime Plus VET analyzer met all manufacturer quality control targets during the study, indicating that the increased variability was most likely the result of matrix effects. Interestingly, we could identify only two studies that compared measurements of serum or plasma electrolytes using direct and indirect ISE methods, and both studies reported a similar degree of variability in measuring Na concentration 15,16 to that observed in our study, suggesting the presence of a matrix effect. The increased variability in our study was not due to abnormal total protein concentrations, but because linear regression did not identify a significant relationship between the difference in serum Cl, K, and Na concentrations measured by the Prime Plus VET and Beckman chemistry analyzers and serum total protein concentration.…”
Section: Discussionsupporting
confidence: 68%
“…In cases of hyperlipidemia and hyperproteinemia, Na, K and Cl are measured as falsely low by the indirect method, whereas the direct method is unaffected (2). As in the study of Chopra et al, Na and K values measured by the direct method were higher than the autoanalyzer results (36). Contrary to the information in distinction was not fully observed for some other tests.…”
Section: Discussionmentioning
confidence: 75%
“…The indirect ISE measurement technique uses a predetermined volume of ionic solution to dilute the plasma sample, usually adjusting the assay concentration by a fixed factor of 0.93 to account for the effect of plasma composition. Abnormal concentrations of proteins or other Non-aqueous components can introduce errors by altering the plasma water content (18,19). An estimated 1/4 of indirect ISE ICU plasma sodium measurements differ from the corresponding direct ISE values by at least 4 mmol/L, the dominant factor being indirect ISE overestimation associated with hypoproteinemia (20).…”
Section: Discussionmentioning
confidence: 99%